Restorative Performance and the Resocialization of Convicted Persons - Batrićević, Ana; Kovačević, Marina (Zbornik Instituta za kriminološka i sociološka istraživanja, 2021)
Relying on up-to-now successful utilization of art (theatre, literature, painting) for the purpose of resocialization and social reintegration of convicted persons, the authors of this paper, discuss the introduction, in theory as well as in practice, the term of restorative performance, as an innovative approach to work with offenders. After analysing the term and characteristics of restorative process, on the one hand, and performance (with focus on theatre performance) on the other, the authors single out key common features of these two processes and derive the definition of a restorative performance. Furthermore, the authors present the examples of successful application of this method of work with convicted persons in Serbia, analysing, on the basis of previously conducted qualitative research, key restorative elements that can be distinguished within them, as significant factors of crime prevention. As the main purpose of this paper, the authors advocate for a broader application of restorative performance and its introduction to regular treatment programmes in institutions for the execution of criminal sanctions in Serbia, with the engagement of all relevant stakeholders and the support of the community.